The analytic hospitality executive : implementing data analytics in hotels and casinos - McGuire, Kelly A. (Hoboken, New Jersey : John Wiley & Son, Inc., 2017)
The Analytic Hospitality Executive helps decision makers understand big data and how it can drive value in the industry. Written by a leading business analytics expert who specializes in hospitality and travel, this book draws a direct link between big data and hospitality, and shows you how to incorporate analytics into your strategic management initiative. You'll learn which data types are critical, how to identify productive data sources, and how to integrate analytics into multiple business processes to create an overall analytic culture that turns information into insight. The discussion includes the tools and tips that help make it happen, and points you toward the specific places in your business that could benefit from advanced analytics. The hospitality and gaming industry has unique needs and opportunities, and this book's targeted guidance provides a roadmap to big data benefits. Like most industries, the hospitality and gaming industry is experiencing a rapid increase in data volume, variety, and velocity. This book shows you how to corral this growing current, and channel it into productive avenues that drive better business. Although the industry is just beginning to recognize the value of big data, it's important to get up to speed quickly or risk losing out on benefits that could drive business to greater heights. The Analytic Hospitality Executive provides a targeted game plan from an expert on the inside, so you can start making your data work for you.
1.Building a strategic analytic culture in hospitality and gaming -- 2.Data management for hospitality and gaming -- 3.Data visualization -- 4.From reactive to proactive decision making: advanced analytics in action -- 5.Analytics for operations -- 6.Analytics for marketing -- 7.Analytics for sales -- 8.Analytics for revenue management -- 9.Analytics for performance analysis -- 10.Analytics for gaming -- 11.Pulling it all together: building an analytical organization.
Includes bibliographical references and index.
Keywords: BIG DATA